MENILAI TINGKAT KESEHATAN PT BANK RAKYAT INDONESIA (PERSERO) TBK TAHUN 2019-2023 MENGGUNAKAN PERBANDINGAN METODE CAMEL DAN METODE RGEC - Nova Kamelia; Very Andrianingsih (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2026)
Bank health is the ability of a bank to fulfill activities and obligations that must be carried out by banks based on applicable regulations. This study aims to determine the health level of PT Bank Rakyat Indonesia (Persero) Tbk 2019-2023 using the CAMEL Method and the RGEC Method and their comparison. The CAMEL method uses assessment aspects such as Capital, Asset Quality, Management, Earnings, and Liquidity; while the RGEC method uses research aspects such as Risk Profile, Good Corporate Governance (GCG), Earnings and Capital. This research was conducted with quantitative research methods using a descriptive approach. The sampling technique uses saturated sampling. The data analysis technique used in this research is CAMEL and RGEC methods. The results showed that (1) the level of health using the CAMEL method in the Capital aspect is “Very Healthy”, the Asset Quality aspect is “Healthy”, the Management aspect is “Healthy”, the Earnings aspect is “Healthy” but the BOPO ratio for 5 years is in an “Unhealthy” condition, the Liquidity aspect is “healthy” (2) the level of health using the RGEC method in the Risk Profile aspect is “Healthy”, Good Corporate Governance aspect “Healthy”, earnings aspect “Very Healthy”, Capital aspect “Very Healthy” (3) the CAMEL method of analysis focuses on operational efficiency and the quality of management which shows improvement while the RGEC method of analysis is more thorough on governance and risk profile. Keywords: CAMEL Method; RGEC Method; Banking Health Level